2004
DOI: 10.1016/s1053-2498(03)00310-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical and psychological attributes of fatigue in female heart transplant recipients

Abstract: Background:The attributes of fatigue after orthotopic heart transplantation (OHT) are poorly understood. We conducted this study to assess the prevalence, severity and correlates of fatigue among female OHT survivors. Methods:Fifty women (age 54.7 Ϯ 13.0 years) from a single heart transplant center, who underwent OHT 5.1 Ϯ 4.4 (mean Ϯ SD) years earlier, completed a battery of questionnaires including the Profile of Mood States-fatigue sub-scale to assess levels of fatigue, the Beck Depression Inventory to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…One notable study described moderately high levels of fatigue in women at Ͼ1 year after heart transplantation. 44 In the same study, fatigue was further found to be correlated with older age and depression. 44 Given the complex nature of fatigue, assessment needs to include consideration of both physiological and psychological components with subsequent targeted recommendations for therapy.…”
Section: Discussionmentioning
confidence: 82%
“…One notable study described moderately high levels of fatigue in women at Ͼ1 year after heart transplantation. 44 In the same study, fatigue was further found to be correlated with older age and depression. 44 Given the complex nature of fatigue, assessment needs to include consideration of both physiological and psychological components with subsequent targeted recommendations for therapy.…”
Section: Discussionmentioning
confidence: 82%
“…18 -21 They frequently describe new physical symptoms that cause distress post-transplant, arising primarily as immunosuppressant side effects (e.g., altered body appearance). 16,19,22,23 Heart transplant (HTx) recipients' physical functioning remains high for up to 9 years post-transplant 12,24 -26 Limited data through the early years after lung transplant (LTx) suggest similarly maintained benefits, whereas heart-lung transplant (HLTx) recipients show renewed impairments over time. 15,27,28 Key predictors/correlates of poorer physical functional outcomes post-transplant are displayed in Table 1 outcomes ( Table 2).…”
Section: Summary Of Major Findings From Psychosocial Outcomes Researcmentioning
confidence: 99%
“…While fatigue severity and sleep disturbances have been studied extensively in other patient populations, their assessment in KTx patients has not kept pace (11–15). Further evaluation of these clinical issues in KTx patients is important because they have the potential to compromise otherwise favorable QOL outcomes achieved by transplantation.…”
mentioning
confidence: 99%